(untitled) (Eurasian Journal of Engineering and Technology, 2023)
With the rapid growth of the Internet of Things (IoT) market and its requirements, low power wide area (LPWAN) technologies are becoming popular. Longdistance wide area network (LoRa WAN) is mainly operated by private companies or organizations, in order to solve two major problems, the trust of private network operators and the lack of network coverage. This study aims to propose a conceptual architecture design for an embedded blockchain solution for LoRa network servers to solve the mentioned problems. Blockchain technology was created and merged with LoRa technology by programming the blockchain in the Java coding language and creating interfaces so that the client may dictate the data within to enable transferring activities to another person without the need of a third party, i.e. Blockchain technology is an open, trustworthy, decentralized, and tamper-resistant system, the most important process in the blockchain, and it is the hashing process, i.e. the encryption of the block. This encryption prevents the data in this block from being modified during any coming period in the future. after filling out the interface, it is distributed to the rest of the nodes in record time using LoRa technology. The delivery of vital and confidential data was implemented and tested using blockchain software and LoRa devices of the type TEL0114, at a frequency of (433) MHZ ,Two-way communication, transparent serial data transmission.. several tests were carried out in order to confirm the efficacy of the proposed system, The data was transmitted over various distances, and the speed of data exchange was increased by eliminating the need for an intermediary; it is a direct procedure from sender to recipient, and it will take much less time to transfer funds between individuals while maintaining the confidentiality of the transfer process